Zanzibar's Liberation between Global 60's and Local politics - Ghazal, Amal N. (MEC Friday Seminars, 2023)
Keywords: Vie politique -- Zanzibar -- 1963-1964

Self-Minoritization: Performing Difference in Colonial Algeria - Ghazal, Amal N. (Comparative Studies of South Asia, Africa and the Middle East, 2021)
This article looks at the process through which the Ibadi Mzabi community in the Algerian desert "minoritized" itself during the colonial period, leading into the 1948 elections to represent the Mzab Valley on the newly created Algerian Assembly. This representation legally and effectively incorporated the Mzab into French Algeria and ended its special status as a French protectorate. Mzabi self-minoritization, Ghazal argues, was a process of performative differentiation based on a sectarian identity. It was initiated by the colonized and negotiated with the colonizer, emerging at the intersection of colonialism and the institutionalization of political representation in colonial Algeria. Ghazal defines this process as self-minoritization to attribute a proactive role for, and more agency to, the colonized in claiming a "minority" identity and negotiating a special status within the colonial order.

Dynamics of Ibadi Reform and the Network as a Methodology - Ghazal, Amal N. (3rd Ibadi Summer School : "Ibadi Islam: A Critical Examination of Sources", 2020)
Keywords: Réformisme

تعليق وإحاطة سياقية على هامش محاضرة د. أمل غزال حول بعض مضامين محاضرتها بعنوان: التكوين الذاتي للأقلية: المزابيون وأداء الاختلاف في المستعمر الفرنسية" - حجاج, قاسم بن حمو (2022)
تعتبر الدراسات المتعلقة بتاريخ الأفكار والأيديولوجيات مجال خصب تحليل الأوضاع والتوجهات الماضية والحاضرة والمستقبلية للمجتمعات، وبالاستناد إلى تدريسي الطويل لمادة الفكر السياسي الحديث والمعاصر ولمادة الأقليات والأمن الدولي. ولما كانت الباحثة قد اشتغلت في مراكز أبحاث أمريكية على الأقليات وخاصة الجماعة المزابية في شمال إفريقيا فإنه لا يمكن استبعاد الدور التمهيدي لمثل هذه لمشاريع البحثية على سياسات القوى الكبرى وحتى الإقليمية كقطر وإسرائيل والإمارات في صنع الأقليات والتلاعب بالتركيبات المجتمعية، علما أن للباحثة أعمال علمية سابقة منشورة عن المزابيين منها دورهم في شمال إفريقيا إبان الحرب العالمية الثانية وعلاقاتهم الخارجية بدويلة طرابلس وبتونس...

Ibadi Muslims of North Africa: Manuscripts, Mobilization, and the Making of a Written Tradition By Paul M. Love Jr - Ghazal, Amal N. (Journal of Islamic Studies, 2021)
Typically, siyar in the Islamic tradition are biographical texts outlining the life and times of individuals, whether scholars or otherwise. Siyar are not known to offer coherent historical narratives, nor are they complete historical chronicles. They are usually compiled in an incremental manner, passing from one generation to another, creating a chain of individuals and/or communities across time and space. Despite their prominence, they have mostly served the historical profession, more or less, as biographical dictionaries. Ibadi siyar in North Africa belong to this same genre and have served a similar purpose. Paul Love’s book uses an innovative methodology in his analysis of siyar that changes the way historians can use and read these texts.
Keywords: Recension

Transmission of Ibāḍī Knowledge: Between China and Oman - Ghazal, Amal N. (The Silk Roads between China and Oman: Networks of Communication and Transmission of Ibadi Knowledge, 2021)

الاقلية الذاتية للمنزابيين في الفترة الاستعنارية عزض ومناقشة: الجزء الأول - خواجة, عبد العزيز بن محمد (2022)
Keywords: Recension